Screening of Bacteriocin production from moderately halophilic skin isolates to inhibit moderately halophilic bacteria producing protease and lipase - (:unkn) unknown (American Leather Chemists Association, 2018)
Bacteriocins, produced from a wide variety of microorganisms to inhibit or kill different species of bacteria, have received increased attention in different industries. Hence, bacteriocins produced from moderately halophilic skin isolates were examined to demonstrate their inhibitory effect against enzyme-producing (protease or lipase) skin isolates. Eleven identified skin isolates, obtained from salted goat and sheep skins, were used as test isolates. Ten of these isolates (Halomonas halodenitrificans, Halomonas halmophila, Salimicrobium salexigens, Gracilibacillus dipsosauri, Salinivibrio costicola subsp. alkaliphilus, Halomonas venusta, Planococcus rifietoensis, Marinococcus tarijensis, Halomonas eurihalina, Staphylococcus arlettae) showed antimicrobial effect against each other. Although Halomonas halodenitrificans, Salimicrobium salexigens, Halomonas venusta did not produce enzyme, the other isolates produced protease or lipase enzymes. While bacteriocin produced from Halomonas halodenitrificans was found to be effective against enzyme-producing Gracilibacillus dipsosauri, Planococcus rifietoensis and Halomonas eurihalina, bacteriocin of Salimicrobium salexigens was effective against enzyme-producing Salinivibrio costicola subsp. alkaliphilus, Marinococcus tarijensis and Halomonas eurihalina. Bacteriocin of Halomonas venusta was effective against enzyme-producing Halomonas halmophila, Marinococcus tarijensis, Halomonas eurihalina, Idiomarina loihiensis and Staphylococcus arlettae. The maximum bacteriocin production of these skin isolates was obtained at 37°C, pH 7.0, and 10% salt concentration. Antimicrobial activities of the bacteriocins against all test isolates were detected at 10°C-60°C, pH 6.0-8.0 and 3%-20% salt concentrations. Antimicrobial activities of all bacteriocins against test isolates were not detected after the treatment with proteinase K. Minimal inhibitory concentration (MIC) values of the bacteriocins against the test isolates were detected as 1/2, 1/4 or 1/8. Scanning electron micrographs of sheepskins showed that sterile bacteriocins of Halomonas halodenitrificans, Salimicrobium salexigens, Halomonas venusta may be used in leather industry to prevent the growth of protease and lipase producing moderately halophilic bacteria. © 2018 American Leather Chemists Association. All rights reserved.